THE EFFECT OF DEMOCRATIC LEADERSHIP STYLE, ORGANIZATIONAL CULTURE COMMITMENT ON ORGANIZATION AND SELF-CONFIDENCE ON LECTURERS’ PERFORMANCE OF STKIP HAMZANWADI SELONG LOMBOK TIMUR REGENCY - Murcahyanto, Hary; Asmawi, Moch.; Madhakomala, R. (JERAM, 2018)
The purpose of this study was to know how was the influence of democratic leadership style, organizational culture, commitment to the organization, confidence, and lecturers’ performance. How did the organizational culture affect organizational commitment, self-confidence, and lecturer performance. How did the organization's commitment to self-esteem, and how did it affect the learners’ performance.This paper was based on the results of research conducted at STKIP Hamzanwadi Selong college which was domiciled in Pancor Selong Sub-district, Lombok Timur regency of Nusa Tenggara Barat Province using survey method, taking samples from one population and using questionnaire as the instrument. Data collection technique was done through questionnaire with descriptive-verification design. The grain validity test is performed through empirical tests of instrument grains. The collecting data were analyzed using F- test and t-test. The results of testing hypothesis and data analysis showed that the democratic leadership style had a significantly influence on organizational culture, commitment to the organization, confidence and lecturers’ performance. Organizational culture had a significantly effect on commitment to the organization, confidence and lecturers’ performance. Commitment to the organization did  not have a positive effect on self-confidence, and confidence did not affect the lecturers’ performance.